Gastrointestinal flora and serum metabolomic elucidation of Astragali Radix water decoction intervention in subclinical bovine mastitis - Yan, Jianpeng; Zhou, Ke; Ma, Ting; Ji, Peng; Wei, Yanming (Frontiers in Veterinary Science, 2025)
BackgroundThis study addresses the global challenge of subclinical bovine mastitis (SCBM) in dairy cows, a prevalent disease causing substantial economic losses, by investigating the mechanistic basis of Astragali Radix, a traditional herbal remedy with empirically validated efficacy but incompletely understood modes of action.MethodsInitially, the active components of Astragali Radix were identified using LC-MS/MS. Dose-response trials were conducted in Holstein cows (n = 24 SCBM cases; n = 6 healthy controls), along with multi-omics integration, including 16S rRNA sequencing for rumen/feces microbiota and UHPLC-MS metabolomics for serum analysis. The therapeutic effects of Astragali Radix water decoction (ARWD) on milk production, inflammatory markers, immune parameters, and oxidative stress were systematically evaluated.ResultsARWD administration dose-dependently improved milk yield and protein content while reducing somatic cell counts. Serum pro-inflammatory cytokines (TNF-α, IL-6, IL-1β) decreased, contrasting with increases in immunoglobulins (IgA, IgM, IgG) and enhanced superoxide dismutase activity. Microbiota restructuring featured ruminal enrichment of Bifidobacterium and fecal dominance of Rikenellaceae_RC9_gut_group, coupled with suppression of pro-inflammatory taxa (e.g., Christensenellaceae_R-7_group). Metabolomic analysis identified four ARWD-responsive biomarkers, notably Spirotaccagenin and Pelanin, operating through linoleic acid metabolism and phospholipase D signaling pathways. Strong correlations linked microbial shifts to improved lactation parameters and reduced inflammation.ConclusionThe findings establish that ARWD alleviates SCBM through coordinated microbiota remodeling and metabolic reprogramming, specifically enhancing antioxidant defenses, restoring mammary barrier integrity, and modulating immune-inflammation crosstalk, with optimal efficacy at 0.4 g·kg−1·d−1 dosage. This mechanistic validation positions ARWD as a scientifically grounded, eco-friendly alternative for sustainable mastitis management, reconciling therapeutic effectiveness with agricultural economic priorities.